Impact of durable ventricular assist devices on post‐transplant outcomes in adults with congenital heart disease. (18th October 2019) - Cedars, Ari; Burchill, Luke; Roche, S. Lucy; Menachem, Jonathan; Axsom, Kelly; Tecson, Kristen; ,
Abstract: Background: There are no published data on post‐transplant outcomes in durable ventricular assist device (VAD)‐supported adult congenital heart disease (ACHD) patients. Methods: We compared post‐transplant outcomes in VAD‐supported vs non‐VAD‐supported ACHD patients using the Scientific Registry of Transplant Recipients. Results: At 1 year, there was no difference in post‐transplant mortality between VAD‐supported (12 patients) and non‐VAD‐supported (671 patients) ACHD patients. Conclusions: In appropriate ACHD patients, VAD use as a bridge to transplant is a reasonable strategy.